Histomorphometric, Immunohistochemical, Ultrastructural Characterization of a Nano-Hydroxyapatite/Beta-Tricalcium Phosphate Composite and a Bone Xenograft in Sub-Critical Size Bone Defect in Rat Calvaria - da Silva Brum, Igor (Materials (Basel), 2020)
Nowadays, we can observe a worldwide trend towards the development of synthetic biomaterials. Several studies have been conducted to better understand the cellular mechanisms involved in the processes of inflammation and bone healing related to living tissues. The aim of this study was to evaluate tissue behaviors of two different types of biomaterials: synthetic nano-hydroxyapatite/beta-tricalcium phosphate composite and bone xenograft in sub-critical bone defects in rat calvaria. Twenty-four rats underwent experimental surgery in which two 3 mm defects in each cavity were tested. Rats were divided into two groups: Group 1 used xenogen hydroxyapatite (Bio Oss™); Group 2 used synthetic nano-hydroxyapatite/beta-tricalcium phosphate (Blue Bone™). Sixty days after surgery, calvaria bone defects were filled with biomaterial, animals were euthanized, and tissues were stained with Masson’s trichrome and periodic acid–Schiff (PAS) techniques, immune-labeled with anti-TNF-α and anti-MMP-9, and electron microscopy analyses were also performed. Histomorphometric analysis indicated a greater presence of protein matrix in Group 2, in addition to higher levels of TNF-α and MMP-9. Ultrastructural analysis showed that biomaterial fibroblasts were associated with the tissue regeneration stage. Paired statistical data indicated that Blue Bone™ can improve bone formation/remodeling when compared to biomaterials of xenogenous origin.